Splenectomy Leads to Amelioration of Altered Gut Microbiota and Metabolome in Liver Cirrhosis Patients - Liu, Yang; Li, Jun; Jin, Ye; Zhao, Lei; Zhao, Fuya; Feng, Jing; Li, Aidong; Wei, Yunwei (Frontiers in Microbiology, 2018)
Dysbiosis of gut microbiota and metabolome is a frequently encountered condition in liver cirrhosis (LC) patients. The severity of liver dysfunction was found to be correlated with the degree of microbial dysbiosis. Several clinical studies have indicated liver function improvement after therapeutic splenectomy for LC induced hypersplenism. We sought to determine whether such post-splenectomy outcome is pertinent to modulation of the abnormal gut microenvironment in LC patients. A cross-sectional study including 12 LC patients and 16 healthy volunteers was first conducted, then a before-after study in the cohort of patients was carried out before and six months after splenectomy. Faecal samples were collected in hospital. Temporal bacterial (n=40) and metabolomics (n=30) profiling was performed using 16s rRNA gene sequencing and UPLC/MS respectively. Our results revealed that microbial composition in patients was clearly different from that in healthy controls, evidenced by considerable taxonomic variation. Along with improved liver function (Child-Pugh score), the patients also displayed similar gut microbiota profile and predicted metagenome function to that of healthy controls after splenectomy. Enterobacteriaceae and Streptococcaceae, two LC-enriched families showing positive relation with Child-Pugh score, exhibited significantly decreased abundance after splenectomy. At the genus level, 11 genera were differentially abundant between patients and healthy controls, but 9 genera of them restituted to normal levels by certain degree after splenectomy. PICRUSt analysis showed the relative abundance of 17 KEGG pathways were partially restored after splenectomy. Four of them were Amino acid related pathways: Lysine degradation, Tryptophan degradation, Amino acid metabolism and Protein digestion and absorption. These findings were supported by metabonomics results which showed that relative abundance of Amino acid and corresponding catabolites changed towards normal. In addition to the variations in the relative abundances of bacteria and metabolites, the correlation between them also altered in patients after splenectomy. Dysbiosis in gut microbiome and related metabolism of LC patients were partially corrected after splenectomy. Whether the improved gut microenvironment could prevent LC related complications and delay the progress of liver cirrhosis is a propitious objective for future study.